2013
DOI: 10.1136/jfprhc-2012-100376
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UK Medical Eligibility Criteria implementation on prescribing of combined hormonal contraceptives

Abstract: ObjectivesCombined hormonal contraceptives (CHCs) are the most widely prescribed contraceptive methods in the UK; however, their use is associated with significant cardiovascular risk for women with some medical conditions and risk factors. The objective of this study was to assess the potential change in CHC prescribing among higher-risk women following publication of the UK Medical Eligibility Criteria for Contraceptive Use (UKMEC) in 2006.MethodsA cross-sectional study was conducted using the General Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
(9 reference statements)
2
12
0
Order By: Relevance
“…In the context of migraine and CHCs use, it is very important to remember that the World Health Organization Medical Eligibility Criteria for Contraceptive Use stated that MA at any age is an absolute contraindication to the use of COCs (WHO Category 4) [46]. The US/WHO MEC is more restrictive than the UK/WHO MEC as regard to MO, rating CHCs as a category 4 for any migraineur over age 35 [47]. That being so, the personal risk assessment should guide the prescription of CHCs in selected conditions.…”
Section: Reviewmentioning
confidence: 99%
“…In the context of migraine and CHCs use, it is very important to remember that the World Health Organization Medical Eligibility Criteria for Contraceptive Use stated that MA at any age is an absolute contraindication to the use of COCs (WHO Category 4) [46]. The US/WHO MEC is more restrictive than the UK/WHO MEC as regard to MO, rating CHCs as a category 4 for any migraineur over age 35 [47]. That being so, the personal risk assessment should guide the prescription of CHCs in selected conditions.…”
Section: Reviewmentioning
confidence: 99%
“…12 A study conducted in the United Kingdom found that with the use of WHO-endorsed WHO, there was a decrease in combined hormonal contraceptive prescriptions for women who were in Categories 3 and 4 for MAC use, however, the method was still prescribed for women who possessed Risk of developing cardiovascular disease. 13 Often, the small range of contraceptive methods in health services justifies this reality, as well as the client's resistance to changing methods.…”
mentioning
confidence: 99%
“…In 2013 Briggs et al 4 determined a statistically significant reduction in the number of higher-risk users (women who were deemed to have a condition which is a UKMEC Category 3 or 4 for CHC use) from 2005 to 2010 following the publication of the UKMEC in 2006. Given that different databases [THIN and GPRD (General Practice Research Database)] were utilised, this study would have provided an opportunity for comparison.…”
mentioning
confidence: 99%